Analisis Aspek Teknik Atau Operasional UMKM Anisa Collection di Klampis Bangkalan dalam Perspektif SKB Syariah - Luk Luus Syarifah (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2024)
For this reason, micro, small and medium enterprises (MSMEs) have an important role in the running of the Indonesian economy. However, MSME governance in general is not well organized and systematic. A feasibility study is needed to determine whether an idea or concept is viable. The aspect or perspective in question is the technical or operational aspect. suggestions need to be carried out with promotions that attract more investment in decoration. This research is field research (field research) which is descriptive analytical in nature. In this research, data found in the field is presented and analyzed to obtain correct and accurate conclusions. To obtain data in this research, qualitative research methods were used. From the results of the research and discussion above, it can be concluded that the feasibility analysis of Anisa Cilection's business from technical or operational aspects shows that this business is feasible to run. In the technical or operational aspect, the Anisa Collection shows feasibility with a strategic location, well-maintained equipment, and a production process that is in accordance with the business feasibility study. It can be concluded that the Anisa Collection shows feasibility with a strategic location, well-maintained equipment , as well as production processes that are in accordance with business feasibility studies. but more attractive promotions need to be carried out to attract consumers' attention, investment in decoration is needed. Good decoration can improve the image of the business. Thus, it is hoped that this business can continue to develop and maintain its position well.